Proyecto de factibilidad para la creación de una empresa productora de té de jícama y su comercialización en la ciudad de Riobamba, provincia de Chimborazo. - Saa Hernández, Marco Vinicio (2010)
The present investigation is to develop the city of Riobamba, targeting the submission of a proposal for the creation of a company producing and marketing Jcama pVT in the city of Riobamba Chimborazo province. In the introduction is a brief ANALYSIS of the situation of our province as it relates to industry. There follows in the Materials and techniques are presented Mtodos of informaciny recoleccin of the Mtodos for research that helped us to present the results of our work. The market is aplicencuestas 295 to 399 persons and establishments in the city of Riobamba, merchants of this product, logrndose determine that is in high demand, in the supply we need to expend the product it holds , grocery stores and commissaries, who acquired them from the cities of Quito and Guayaquil that is manufactured. As for the engineer of the project presents the production process in all its phases, in terms tamaoy localizacin is attached a map of the distribucinfsica of the plant. Adems indicated that the company estarubicada in the North of the city of Riobamba at the time that you deploy. The financial study presents the financing inversiny, Ascom evaluacin financial indicators of the project, which determines that it is advisable to implementacin of this company. Regarding the administrative organization has planned a limited liability company, by the favorable conditions presented by this type of company.